HIBRIDITAS POSTKOLONIALISME HOMI K. BHABHA Dalam Novel Midnight’s And Children Salman Rushdie - Syihabul Furqon; NFN Busro (JENTERA: Jurnal Kajian Sastra, 2020)
Postcolonialism is a branch of the cultural studies that focuses on socio-cultural analysis, including signs and languages. Colonialism had clear implications in the actions of postcolonial society. Homi K. Bhabha found identification that in postcolonialism there emerged what he called as hybridity. Hybridity is a cross-culture (both intrinsic and extrinsic) that appears in society in many forms, one of which is language and attitude. This research will review Salman Rushdie's Midnight’s Children novel to reveal which aspects are hybridities. As a methodological tool, the authors use descriptive analysis (intrinsic-extrinsic). In this study, the authors found a large number of hybridity identifications in the novel Midnight’s Children. Especially in the aspects of identity (especially the formation of the subject), language, and inner struggle of characters in the novel. AbstrakPoskolonialisme merupakan cabang kajian studi budaya yang berfokus pada analisis sosiokultural, termasuk tanda-tanda dan bahasa. Kolonialisme memunculkan implikasi yang terbaca jelas dalam tindakan masyarakat poskolonial. Homi K. Bhabha menemukan identifikasi bahwa dalam poskolonialisme muncul apa yang disebutnya sebagai hibriditas. Hibriditas adalah silang budaya, baik intrinsik maupun ekstrinsik, yang muncul di masyarakat dalam banyak bentuk, seperti bahasa dan sikap. Dalam penelitian ini akan ditinjau novel Midnight’s Children karya Salman Rushdie untuk mengungkapkan aspek mana saja yang merupakan hibriditas. Sebagai alat metodologi, penulis menggunakan analisis deskriptif (intrinsik-ekstrinsik). Dalam penelitian ini penulis menemukan sejumlah identifikasi hibriditas dalam novel Midnight’s Children, terutama dalam aspek identitas (pembentukan subjek), bahasa, serta pergulatan batin tokoh..